HUBUNGAN ANTARA LINGKUNGAN KELUARGA DENGAN SIKAPSISWA KELAS V SEKOLAH DASAR NEGERI PURWOMARTANI, KALASAN KABUPATEN SLEMAN - Hardiman Hardiman (Universitas PGRI Yogyakarta, 2015)
This study aimed to determine whether there is a relationship between the family and the attitude of fifth grade students Purwomartani State Primary School, KalasanSleman. Of the 56 respondents who provided information obtained data on the number offamily members; father's education level; mother's education level; and the atmosphere ofthe student residence. In order to answer that has been filed, the data were analyzed byusing Pearson Product Moment. Based on the analysis of obtained results of the study asfollows: (1) the correlation number of family members obtained results rhitung 0.213with significance level of 5% and rkritik showed 0.264. Thus there is no significantrelationship between the number of family members with students' attitudes towards theenvironment around the school. (2) correlation father's level of education obtainedrhitung 0.874 with significance level between father's education level obtained rhitung0,874dengan significant level of 5% and rkritik shows the number 0.264. Thus there is asignificant relationship between the father's education level students' attitudes towards theenvironment around the school (3) correlation tingkst Mother education obtained rhitung0.850 with significance level of 5% and rkritik shows the number 0,624. Thus there is asignificant relationship between the level of maternal education with students' attitudestowards the environment and rkritik 5% indicates the number 0.624 with significancelevel of 5% and rkritik shows the number 0,624. Thus there is a significant relationshipbetween the atmosphere of a place to stay with the students' attitudes toward schoolenvironment. In connection with the research that has been done school. (4) thecorrelation atmosphere student residence obtained rhitung 0.738 with significance levelto conclude, that (1) the number of family members does not affect students 'attitudestoward school environment (2) the father and mother education level influence students'attitudes toward school environment and (3) atmosphere of residence a huge influence onthe attitudes of students to the school environment.